Research on the role of internal audits in ensuring the effectiveness of internal control systems in the Turkish public sector - Kukrer, Engin; Saglam, Necdet (Journal of Accounting, Business and Finance Research, 2023)
The purpose of this research is to investigate the role of internal audit units in Turkish public administrations in ensuring and improving the effectiveness of their internal control systems within the framework of the internal control components of the Public Internal Control Standards, determined on the basis of the COSO (Committee of Sponsoring Organizations of the Treadway Commission) model. In our study, the survey method was used to collect data, and questions were answered according to a five-point Likert scale. In order to obtain evidence for the construct validity of the developed scale, a factor analysis was performed, and the components were examined in line with the factor analysis. In this context, statistical data obtained for each research question were examined with a one-way analysis of variance, a t-test and a factor analysis to determine whether there was a significant difference according to gender, experience in the field of auditing, education level, type of administration, or certification variables. The survey study was conducted among internal auditors who work in public administration in Turkey. It was determined that the internal auditors do not get sufficient support from senior management and employees in terms of organizational structure to ensure the effectiveness of the internal control system.